Fixed Point Result on Generalized \((ψ,φ)_s\)-Contractive Mappings in Rectangular \(b\)-Metric Spaces - Sukprasert, Pakeeta; Kumam, Poom; Thongtha, Dawud; Sombut, Kamonrat (Communications in Mathematics and Applications, 2016)
The aim of this paper is to present the definition of a weak altering distance function and new generalized contractive mapping in rectangular \(b\)-metric spaces. We discuss the fixed point result of such a mapping in rectangular b-metric spaces.